D'àngels i dimonis. Anàlisi d'una seqüència del programa iconogràfic de la moralització enciclopèdica de la fin'amors en el Breviari d'Amor de Matfré Ermangaud. - MARTINES, VICENT (Scripta, 2017)
This paper analyzes three illuminations of Matfré Ermengaud's Breviari d'Amor which represent the author's attempt to Christianize the concept of fin'amors. In particular, they establish a connection among natural history, sacred history and love and lovers and allow us to study who is the recipient of Ermengaud's work. In addition, they serve us to study the author's injunctions on the model to be followed (angels), the model to reject (demons), and the sphere of action of «the evil» : courtly society and the ecosystem of fin'amors.